Proposta de ensino por investigação em física térmica no sistema de organização modular de ensino visando facilitar a aprendizagem significativa - CRUZ, Benildo Antonio Barbosa da (Universidade Federal do Oeste do Pará, 2021)
This Master's dissertation was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) – Finance Code 001 – and aims to investigate the contributions of the application of experiments to facilitate the learning of Thermal Physics in High School and present as a proposal of educational product a Didactic Guide composed of four experimental activities of thermodynamics – Use of the thermometer, the Locke’s Experience, Thermoscope and Dilatometer. These activities are intended to serve as potentially meaningful materials to assist teachers in their physics classes and have been elaborated and applied based on a methodology of Teaching by Research to facilitate Meaningful Learning, according Ausubel’s theory. Our work intends to answer the following question: Can the use of these experimental activities in Thermal Physics contribute to the meaningful learning of SOME students? For this, we apply the educational product in two second grade High School classes in rural communities, both assisted by the Sistema de Organização Modular de Ensino – SOME. The first application took place in the community of Costa do Tapará, which is in the region of the floodplain of the river Amazon, with main access by fluvial route. The second application was in the Santarém Miri community, which is also in the floodplain of the river Amazon, but with main access by land. In both communities, we sought to identify meaningful learning patterns through written reports of students, questionnaires with open questions, questionnaires with closed questions using a Likert scale and socializations, which were performed at the end of each experimental activity. The analysis of the results suggests that the educational product was well accepted by the students contributing to increase their interest in the content and to facilitate the learning of the concepts of thermodynamics in a meaningful way.